2002
DOI: 10.1053/jhep.2002.31354
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment versus endoscopic plus pharmacologic treatment for acute variceal bleeding: A meta-analysis

Abstract: Endoscopic therapy, involving either injection sclerosis or band ligation, is considered the intervention of first choice for acute variceal bleeding (AVB). Pharmacologic agents have also been shown to be highly effective in the control of the bleeding episode. The purpose of this meta-analysis was to assess whether vasoactive drugs may improve the efficacy of endoscopic therapy (injection sclerosis or band ligation) in the control of AVB and thus increase survival rates. Computer databases and scientific meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
2
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(217 citation statements)
references
References 21 publications
4
196
2
15
Order By: Relevance
“…A meta-analysis of 8 trials showed that, compared to endoscopic therapy alone (sclerotherapy or EVL), endoscopic plus pharmacological (octreotide, somatostatin, vapreotide) therapy improved the initial control of bleeding and 5-day hemostasis without differences in mortality or severe adverse events. 105 …”
Section: D2 Specific Measures To Control Acute Hemorrhage and Prevementioning
confidence: 99%
“…A meta-analysis of 8 trials showed that, compared to endoscopic therapy alone (sclerotherapy or EVL), endoscopic plus pharmacological (octreotide, somatostatin, vapreotide) therapy improved the initial control of bleeding and 5-day hemostasis without differences in mortality or severe adverse events. 105 …”
Section: D2 Specific Measures To Control Acute Hemorrhage and Prevementioning
confidence: 99%
“…This consideration supported by a meta-analysis found that the combination of endoscopic therapy and SST or its analogues achieves better haemostasis although without improvement in survival. 34 It has also been demonstrated that the addition of sclerotherapy significantly improves the efficacy of SST alone for the treatment of acute variceal bleeding. 35 The results of our study support the beneficial role of SST in combination with endoscopic therapy but not OCT in the optimal management of BEVs.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis of methodological quality was performed to control any bias in the estimates of intervention efficacy. [13][14][15][16] …”
Section: T He Incidence Of Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%